PENGARUH EDTA DALAM MENGHILANGKAN KADAR KADMIUM YANG TERAKUMULASI DALAM BERBAGAI ORGAN UDANG Macrobrachium sintangense de Man - Agoes Soegianto; M. Yusuf Alamudi; Miftakhul Ulum; Eko W. Putro; Nining D. Widyayanti (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2003)
The objective of experiment is to know capability of EDTA to reduce the concentration of cadmium, which accumulated in Macrobrachium sintangense organ. Two groups of shrimps were exposed to 30 mg/L and to freshwater (control) during 7 days and continue with EDTA 0.1 and 1 ppm during 7 days. After finish the experiment, gill, hepatopancreas, carapace and abdominal muscle dissected and destructed with concentrated HNO3 to be analyzed the concentration of cadmium which is accumulated in those organs. The result showed that the concentration of cadmium in gill of control shrimp are 1.696 ± 0.3920 mg/Kg, hepatopancreas 1.1810 ± 0.545 mg/Kg, carapac 0.1025 ± 0.1524 mg/Kg, and abdomen 0.201 ± 0.349 mg/Kg. The concentration of cadmium in exposed shrimps which treated with 0.1 ppm of EDTA are 66.4090 ± 3.22 mg/Kg in gill, 26.4791 ± 0.86 mg/Kg in hepatopancreas, 8.8039 ± 0.66 mg/Kg in carapac; and 3.6324 ± 0.13 mg/Kg in abdomen. The concentration of cadmium in exposed shrimps which treated with 1 ppm of EDTA are 34.8809 ± 4.24 mg/Kg in gills, 9.7290 ± 1.03 mg/Kg in hepatopancreas; 4.6574 ± 0.34 mg/Kg in carapac; and 1.8546 ± 0.43 mg/Kg in abdomen. The greater elimination of cadmium occurs at the shrimp, which is treated with 1 ppm of EDTA.